Marked variation between winter and spring gut microbiota in free-ranging Tibetan Macaques (Macaca thibetana) - Sun, Binghua (Sci Rep, 2016)
Variation in the availability and distribution of food resources is a strong selective pressure on wild primates. We explored variation in Tibetan macaque gut microbiota composition during winter and spring seasons. Our results showed that gut microbial composition and diversity varied by season. In winter, the genus Succinivibrio, which promotes the digestion of cellulose and hemicellulose, was significantly increased. In spring, the abundance of the genus Prevotella, which is associated with digestion of carbohydrates and simple sugars, was significantly increased. PICRUSt analysis revealed that the predicted metagenomes related to the glycan biosynthesis and metabolic pathway was significantly increased in winter samples, which would aid in the digestion of glycan extracted from cellulose and hemicellulose. The predicted metagenomes related to carbohydrate and energy metabolic pathways were significantly increased in spring samples, which could facilitate a monkey’s recovery from acute energy loss experienced during winter. We propose that shifts in the composition and function of the gut microbiota provide a buffer against seasonal fluctuations in energy and nutrient intake, thus enabling these primates to adapt to variations in food supply and quality.